Scenarios of Iranians' participation in leisure time physical activity. Issue 4 (2nd October 2021) - Ziaee, Ali; Aghaei, Najaf; Saffari, Marjan; Zenouz, Reza Yousefi; Van Hilvoorde, Ivo
ABSTRACT: This study aimed to develop scenarios of Iranians' future participation in leisure-time physical activity (LTPA). To this end, 12 experts in the field of leisure, sociology, and sport management were invited to take part. The Decision Making Trial and Evaluation Laboratory (DEMATEL) method was used to organize and analyze the data collected in a questionnaire featuring a pairwise comparison of 18 indicators of LTPA which were drawn from the relevant literature. The DEMATEL was then used to determine the critical uncertainties of the future participation in leisure-time physical activities. Considering the two most important critical uncertainties from economic and technological dimensions, four possible futures around Iranians' participation in these activities were created. By taking the uncertainties into consideration, decision-makers can contribute to the promotion in LTPA in the best and most efficient manner by having knowledge about the most influential framing factors of possible futures.